Influence of lactation stages on erythrocyte osmotic fragility of indigenous Badri cattle of Uttarakhand - SWATI THAKUR; R HUOZHA; S RAMANARAYANAN; S DHARA; A MAITI; S K RASTOGI (Indian Journal of Animal Sciences, 2024)
The aim of this study was to evaluate the influence of lactation stages on erythrocyte osmotic fragility. The study was carried out using forty healthy Badri cows divided into five groups with eight animals in each group during different stages of lactation, viz. 1 (0 to 60 days), 2 (61 to 120 days), 3 (121 to 180 days), 4 (181 to 240 days) and 5 (non-lactating animals) as control animals. The per cent haemolysis of erythrocytes among different lactation groups was found significant at 0.9% during mid and early late lactation i.e. 2 and 3 group and 0.5% saline concentration during all stages of lactation as well as non- lactating animals.